SENP1-mediated deSUMOylation of USP28 regulated HIF-1α accumulation and activation during hypoxia response - Du, Shi-chun (Cancer Cell Int, 2019)
BACKGROUND: The ubiquitin-specific protease 28 (USP28) is an oncogenic deubiquitinase, which plays a critical role in tumorigenesis via antagonizing the ubiquitination and degradation of tumor suppressor protein FBXW7-mediated oncogenic substrates. USP28 controls hypoxia-dependent angiogenesis and metastasis by preventing FBXW7-dependent hypoxia-inducible transcription factor-1α (HIF-1α) degradation during hypoxia. However, it remains unclear how USP28 activation and HIF-1α signaling are coordinated in response to hypoxia. METHODS: The in vitro deubiquitinating activity assay was used to determine the regulation of USP28 by hypoxia. The co-immunoprecipitation and GST Pull-down assays were used to determine the interaction between USP28 and SENP1. The in vivo deSUMOylation assay was performed to determine the regulation of USP28 by SENP1. The luciferase reporter assay was used to determine the transcriptional activity of HIF-1α. RESULTS: Here, we report that USP28 is a SUMOylated protein in normoxia with moderate deubiquitinating activity towards HIF-1α in vitro, while hypoxia and HIF-1α activate USP28 through SENP1-mediated USP28 deSUMOylation to further accumulate HIF-1α protein in cells. In agreement with this, a SUMOylation mutant USP28 showed enhanced ability to increase HIF-1α level as well as control the transcriptional activity of HIF-1α. CONCLUSION: Collectively, our results reveal a novel SENP1–USP28–HIF-1α positive feedback loop to maximize the concentration of HIF-1a protein and amplify its downstream effects during hypoxia response.